Investigation into the Translucency of Tooth-Colored Restorative Materials - H. Torabzadeh; R. Aminian; A. Ghasemi (Tehran University of Medical Sciences, 2009)
Objective: The aim of this study was to investigate the translucency of resin-modified glass-ionomer cements (RMGIC) and polyacid-modified composite resin (PCMR) over a period of one year. Materials and Methods: The study was done on three RMGIC (Fuji II LC, Photac-Fil Aplicap and Vitremer) and one PCMR (Dyract). A conventional GIC (Fuji Cap II) and two composite resins (Tetric and Z 100) were used for comparison. Five discs approximately 5 mm in diameter and 1.5 mm thick were made from each material using a Perspex mould. The specimens were kept in distilled water at 37°C during the test period. The optical density/mm (inverse of translucency) of each material was measured using a special photometric set up after preparation and after one week, six months, and one year. Means and standard deviations were calculated and subjected to Two-way ANOVA, One- way ANOVA and Scheffe tests. Results: The results indicated that all of the materials, except Dyract, showed an increase of translucency over the test period. After one year, the conventional GIC was the least translucent material. Conclusion: The translucency of the resin-modified GICs and Dyract was equivalent to that of the composite resins Tetric and Z 100.